The Bang-Bang sisters : a novel - Youers, Rio (William Morrow, 2024)
"Blood. Bullets. Rock and roll. Meet the Bang-Bang Sisters: Brea, Jessie, and Flo. Together, they're a kick-ass rock band with an unbreakable bond. But that's only half the story. Offstage, they're highly skilled vigilantes, traveling the country in their beaten-up tour van to exact justice on criminals who have slipped through the system. Part rock stars, part assassins, they're a force to be reckoned with. Drawn by a tantalizing lead, the sisters head to Reedsville, Alabama - a city crawling with destitution and corruption - where they close in on a notorious serial killer known as "the wren." But they soon discover that they have walked straight into a trap set by Chance Kotter, a ruthless mobster with a personal vendetta. Bruised and beaten, the sisters find themselves at the mercy of Chance and a sadistic game of survival that will pit them against each other: Forty-eight hours. One city. Three sisters. Only one of them can survive. Full of gripping action and shocking twists that come at a breakneck pace, The Bang-Bang Sisters is a relentless, edge-of-your-seat thrill ride that will leave you breathless." -- Jacket flap